Time and Cost Analysis Using the Fast Track Method in the ITS Bank Building Construction Project - Rudiansyah Rudiansyah; Hanie Teki Tjendani; Erni Puspanantasari (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2025)
Higher education institutions are required to provide a conducive learning environment to produce excellent and competitive human resources. One of the keys supporting factors is the availability of adequate infrastructure, including accessible financial services within the campus. Institut Teknologi Sepuluh Nopember (ITS) responded to this need by constructing a banking building as part of its efforts to create an integrated digital campus ecosystem. However, the project faced significant delays from the original schedule, prompting the need for acceleration strategies that maintain both cost and quality. One such strategy is the Fast Track method, which allows construction activities to be carried out in parallel to shorten the project duration. This study aims to analyze the project’s time and cost using the Fast Track method, a project acceleration technique that enables activities to be performed simultaneously to reduce execution time. The research was conducted on the ITS Banking Building construction project, which has a contract value of Rp 11,871,000,000 and a planned duration of 120 calendar days. The analysis involved identifying critical activities using the Critical Path Method (CPM) and then rescheduling using the Fast Track approach to calculate the optimal time and cost. The results of the study show that the optimal project duration after applying the Fast Track method is 112 working days, which represents a 6.7% reduction from the original 120 days. The optimal cost after acceleration using the Fast Track method is Rp 9,696,512,763, representing a 9.3% reduction from the initial cost of Rp 10,694,683,195pa.